2019
DOI: 10.1002/pro.3598
|View full text |Cite
|
Sign up to set email alerts
|

A stable engineered human IgG3 antibody with decreased aggregation during antibody expression and low pH stress

Abstract: Human IgG comprises four subclasses with different biological functions. The IgG3 subclass has a unique character, exhibiting high effector function and Fab arm flexibility. However, it is not used as a therapeutic drug owing to an enhanced susceptibility to proteolysis. Antibody aggregation control is also important for therapeutic antibody development. To date, there have been few reports of IgG3 aggregation during protein expression and the low pH conditions needed for purification and virus inactivation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 44 publications
1
25
1
Order By: Relevance
“…A fundamentally different approach would be (re‐)engineering of the product's primary structure to increase its tolerance towards acidic conditions (Ducancel & Muller, ; Saito, Namisaki, Hiraishi, Takahashi, & Iida, ; Skamris et al, ). We have shown that a simple method such as ANS fluorescence could be used to identify candidate molecules that have a low propensity to denature under (mildly) acidic conditions and would thus aggregate to a low extent during subsequent neutralization.…”
Section: Discussionmentioning
confidence: 99%
“…A fundamentally different approach would be (re‐)engineering of the product's primary structure to increase its tolerance towards acidic conditions (Ducancel & Muller, ; Saito, Namisaki, Hiraishi, Takahashi, & Iida, ; Skamris et al, ). We have shown that a simple method such as ANS fluorescence could be used to identify candidate molecules that have a low propensity to denature under (mildly) acidic conditions and would thus aggregate to a low extent during subsequent neutralization.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our data shows IgG3 possess superior effector functions over IgG1 that render it well for use in cancer therapy. However, owing to an enhanced susceptibility to proteolysis, shorter half-life than other IgG subclasses and aggregation during bioprocessing, IgG3 has not been used as a therapeutic drug 35 .To circumvent these obstacles engineered human IgG3 anti-CD20 antibodies containing the CH3 constant domain from IgG1 have recently been developed, providing a new arsenal of IgG3 antibodies to explore 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a Lys is present at position 409 in IgG3, but IgG3 is still prone to aggregation under acidic conditions. A recent study has reported that two amino acid mutations in the CH3 domain, N392K and M397V, decreased aggregation during low pH conditions [36]. However, our study only analyzed IgG4 aggregation under low-pH treatment.…”
Section: Plos Onementioning
confidence: 96%